Primary Malignant Peritoneal Mesothelioma Mimicking Ovarian Carcinoma: A Case Report Highlighting the Importance of Immunohistochemistry - Rio Hendra; Tofrizal; Hera Novianti; Yessy Setiawati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Primary malignant peritoneal mesothelioma (PMPM) is an uncommon and aggressive malignancy arising from the mesothelial lining of the peritoneal cavity. The diagnosis of PMPM is often challenging due to its rarity, nonspecific clinical presentation, and histologic similarities to other malignancies, particularly adenocarcinomas. Immunohistochemistry plays a crucial role in differentiating PMPM from metastatic adenocarcinoma, which is essential for accurate diagnosis, appropriate treatment, and prognostication. Case presentation: We present the case of a 43-year-old female who presented with abdominal distension, ascites, and weight loss, initially raising suspicion of ovarian carcinoma. However, histopathological examination of the omental tissue revealed a proliferation of epithelial cells with papillary and glandular-like growth patterns. Immunohistochemical staining demonstrated strong positivity for calretinin, a mesothelial marker, while staining for estrogen receptor (ER) and progesterone receptor (PR) was negative, effectively ruling out an ovarian or endometrial origin. The diagnosis of PMPM, epithelioid subtype, was confirmed. Conclusion: This case underscores the challenges in diagnosing PMPM and highlights the critical role of immunohistochemistry in differentiating it from metastatic adenocarcinoma. Accurate diagnosis is essential for determining appropriate management strategies and providing prognostic information.